Formamide, dimethylformamide – Determination of formamide in urine by gas chromatography mass spectrometry [Biomonitoring Methods, 2018]. Issue 1 (24th January 2018) - Scherer, G.; Gilch, G.; Aust, B.; Blaszkewicz, M.; Göen, T.; Hartwig, A.; ,
Abstract: The working group "Analyses in Biological Materials" of the Permanent Senate Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area verified the presented biomonitoring method. The method described herein allows the determination of formamide in urine by gas chromatography mass spectrometry (GC‐MS). Due to its sensitivity, this method is suitable for the detection of occupational and environmental exposure to formamide. For the analytical determination 1 mL of urine is lyophilised after being spiked with 13 C, 15 N‐formamide as the internal standard. The lyophilisate is extracted with 200 µL methanol. After centrifugation, 1 µL of the extract is injected into a GC‐MS system. The method was extensively validated and the reliability data were confirmed by an independent laboratory, which has established and cross‐checked the whole procedure.